2020
DOI: 10.15324/kjcls.2020.52.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Yogurt: Changes in Blood Components on Healthy Men Smokers

Abstract: Smoking is associated with increased inflammation and is a risk factor for a range of diseases. Conversely, yogurt has beneficial effects on health. This study examined the effects of yogurt consumption on the hematological parameters and fibrinogen levels in smokers. The participants were categorized into four groups. Non-smokers were assigned to the control and yogurt groups while smokers were assigned to the smoking and combined (yogurt plus smoking) groups. The participants consumed yogurt, and either smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…1 -Table 2). Different studies confirmed the positive influence of yogurt consumption on immunity, namely Ajibola et al (2012), Asemi et al (2012), Jafari et al (2016), Leonard (2018), Gasparri et al (2019), Kim et al (2020), Yang et al (2022), and Ravindran et al (2022). Allium sativum (garlic) positively influences the immunity of the organism, modifying the values of vitamin D, erythrocyte distribution width, platelets and platelet distribution width, neutrophil, monocyte, and zinc (C.S.…”
Section: Resultsmentioning
confidence: 95%
“…1 -Table 2). Different studies confirmed the positive influence of yogurt consumption on immunity, namely Ajibola et al (2012), Asemi et al (2012), Jafari et al (2016), Leonard (2018), Gasparri et al (2019), Kim et al (2020), Yang et al (2022), and Ravindran et al (2022). Allium sativum (garlic) positively influences the immunity of the organism, modifying the values of vitamin D, erythrocyte distribution width, platelets and platelet distribution width, neutrophil, monocyte, and zinc (C.S.…”
Section: Resultsmentioning
confidence: 95%